Human capital and development in the Philippines a festschrift in honor of Alejandro N. Herrin - Capuno, Joseph J.; Orbeta, Aniceto C. Jr (Philippine Institute for Development Studies, 2008)
"After many policies have been put in place over the years to uplift the welfare of the Filipinos, the overall human development in the country has not reached its maximum potential. Undoubtedly, much remains to be done, especially in improving the quality of human capital in the Philippines. Policy reforms are needed to improve the access to basic education, provide sufficient work opportunities, strengthen health systems especially in the rural areas, promote child and maternal health and nutrition, and encourage people to practice responsible sexuality and parenthood. The list of gaps can go on, which only reflects the many critical issues that remain unsolved until now. Even how the population should be managed continues to be a controversial, sensitive, and divisive topic. The volume reviews these issues with academic rigor and with an eye toward providing practical policy recommendations. It is a fitting honor to Dr. Alejandro N. Herrin, touted as the "Father of Population and Development" in the Philippines, for his vast research works and institutional capacity-building efforts especially on population management and health issues that have led to many policy initiatives in the country."--Back cover.